2014
DOI: 10.4149/bll_2014_108
|View full text |Cite
|
Sign up to set email alerts
|

The examination of protective effects of gallic acid against damage of oxidative stress during induced-experimental renal ischemia-reperfusion in experiment

Abstract: Abstract:Aim: In this study, probable effects of gallic acid were investigated in experimentally induced renal I/R injury in rats. Material and methods: For this purpose, each group consisted of 7 Spraque dawley male albino rats. Groups were defi ned as follows; Group I: control group; Group II: I/R group; Group III, IV and V: I/R+Gallic acid (50, 100 and 200 mg.kg -1 respectively-i.p.). Left kidney was removed by nephrectomy except for Group I. I/R was induced in the other kidney. Gallic acid was given 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…It has been established that GA has the ability in lowering the systolic blood pressure in rats with essential hypertension, and in providing the protection against NOX2-induced oxidative stress response [12]. Earlier study reveals that GA can provide protection against renal oxidative stress by reducing peroxidation intensity [13]. Besides, high fat diet-induced dyslipidaemia, hepatosteatosis and oxidative stress also can be protected by GA as studied in rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that GA has the ability in lowering the systolic blood pressure in rats with essential hypertension, and in providing the protection against NOX2-induced oxidative stress response [12]. Earlier study reveals that GA can provide protection against renal oxidative stress by reducing peroxidation intensity [13]. Besides, high fat diet-induced dyslipidaemia, hepatosteatosis and oxidative stress also can be protected by GA as studied in rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Senturk and Yıldız (2018); in a renal I/R model, groups treated with antioxidant substance demonstrated a dosedependent decrease in CAT and SOD amounts. Canbek et al (2014) in a study conducted, revealed that the application of antioxidant substances in rats with renal I/R damage (45 min/6h) caused the band densities of SOD and CAT to be decreased. Many similar manuscripts have been found, for example (Bayramoglu et al, 2011), the results of which are in parallel with our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tannic acid inhibits the generation of ROS in irradiation-induced apoptosis in a megakaryocytes model, preventing apoptosis, promoting platelet recovery and raising survival [21]. In the body, tannic acid is metabolized into several derivatives, such as gallic acid or PGG, already known for their beneficial effects against oxidative stress and IRI [22,23].…”
Section: Discussionmentioning
confidence: 99%